The Role of The Public Bureaucracy in Preventing Covid-19 in Indonesia (Public Administrative Perspective) - Henni Zainal; Suparman Mekka; Surianti Surianti; Muhammad Jihad Firman; Maya Kasmita (Universitas Negeri Makassar, 2022)
Indonesia is at present actually battling with Coronavirus, as are different nations on the planet. The quantity of Coronavirus cases keeps on developing for certain individuals announcing recuperation, yet the quantity of positive cases keeps on developing consistently. The reason for this study was to decide the job of the public administration in forestalling Coronavirus in Indonesia. The exploration was led with a subjective methodology with a study technique. Information assortment procedures utilized are meetings and reports. The information investigation method is information examination in the exploration interaction with a few phases that current data is passionately and judiciously founded on information or realities found in the field. The consequences of this study show that the public authority has not had the option to deal with Coronavirus in general, it tends to be demonstrated by the population tainted with Coronavirus expanding yet there are additionally some who have recuperated. The ramifications of this exploration is to work on the coordination of the public authority and state contraption, urban areas, locale, sub-regions and towns with the goal that what the local area needs can be satisfied and Coronavirus can be defeated in the public eye all in all.